Trends in International Student Enrollments in Canadian Community Colleges (Comparative & International Education Series, 2021)
Chapter 13|12 pages Trends in International Student Enrollments in Canadian Community CollegesBy Elizabeth Buckner, Sarah Morales, Taiya Brown, Scott ClerkThis chapter examines trends in international student enrollments in the Canadian community college sector over the past decade. We first provide an overview of the Canadian community college sector and its longstanding mandate of training students for local labor markets. We then discuss how federal, provincial, and institutional authorities have all supported increasing international student enrollments for primarily economic rationales. Next, we draw on data from Statistics Canada to examine recent trends in international student enrollments in the community college sector. We point to three major trends: (1) the unprecedented growth of international student enrollments in the college sector; (2) an increasing proportion of international college students from India; and (3) a high concentration of international college students in only two provinces, namely Ontario and British Columbia. We argue that these trends raise important policy questions for the sector's traditional mandate of local labor market preparation, while also having important implications for how college leaders and student affairs professionals meet the needs of their students.